If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -1k = 8 Solving 3 + -1k = 8 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1k = 8 + -3 Combine like terms: 3 + -3 = 0 0 + -1k = 8 + -3 -1k = 8 + -3 Combine like terms: 8 + -3 = 5 -1k = 5 Divide each side by '-1'. k = -5 Simplifying k = -5
| 69=-8-7(m+3) | | 14x-7=7+10x | | 22-4(3-x)=42 | | 36=(x+3)(x+3) | | 2x^2-10-x=0 | | 0.6x+4=20-x | | 0.6+4=20-x | | 12-w=157 | | 260-w=145 | | -4(b-3)=-44 | | 195=-x+1 | | 36=2x^2+6x+9 | | 4p-31+p+13=P+50 | | 3=-6v+3(v+8) | | -3(z+2)=24 | | 2n^2+n-36=0 | | x+3x+5=12 | | -2(c-1)=18 | | 4x^2+39x+171=0 | | w+12+2w+2=w+50 | | 2.5x-6=-4-3.5 | | -9x^9y^8(-4x^6z^7+3y^3+3z^8)= | | x^2+y^2-2x-8y-47=0 | | -9x^9y^8(-4x^6z^7+3y^3+3z^8)= | | 15x-48+5x=13x | | (x+4)2+(y+4)2=32 | | xcubed-2xsquared+1=0 | | x-2y=28 | | 6=2-8(1-y) | | (x-5)2+(y-5)2=27 | | xcubed-2quared+1=0 | | 44+q+41=8q+28 |